Uncovering the Relationship Between Genes and Phenotypes Beyond the Gut in Microvillus Inclusion DiseaseSummary - Mingyue Sun; Olena Pylypenko; Zhe Zhou; Mingqian Xu; Qinghong Li; Anne Houdusse; Sven C.D. van IJzendoorn (Cellular and Molecular Gastroenterology and Hepatology, 2024)
Microvillus inclusion disease (MVID) is a rare condition that is present from birth and affects the digestive system. People with MVID experience severe diarrhea that is difficult to control, cannot absorb dietary nutrients, and struggle to grow and thrive. In addition, diverse clinical manifestations, some of which are life-threatening, have been reported in cases of MVID. MVID can be caused by variants in the MYO5B, STX3, STXBP2, or UNC45A gene. These genes produce proteins that have been functionally linked to each other in intestinal epithelial cells. MVID associated with STXBP2 variants presents in a subset of patients diagnosed with familial hemophagocytic lymphohistiocytosis type 5. MVID associated with UNC45A variants presents in most patients diagnosed with osteo-oto-hepato-enteric syndrome. Furthermore, variants in MYO5B or STX3 can also cause other diseases that are characterized by phenotypes that can co-occur in subsets of patients diagnosed with MVID. Recent studies involving clinical data and experiments with cells and animals revealed connections between specific phenotypes occurring outside of the digestive system and the type of gene variants that cause MVID. Here, we have reviewed these patterns and correlations, which are expected to be valuable for healthcare professionals in managing the disease and providing personalized care for patients and their families.